Contextual Learning of Islamic Religious Education in the Wasiat “Ingsun Titip Tajug Lan Fakir Miskin” - Achmad Muhajir; Eddy Saputra (Permata : Jurnal Pendidikan Agama Islam, 2025)
Sunan Gunung Jati is an important figure in the spread of Islam in the Cirebon region, a city and district at the northern tip of West Java. There are messages left to be studied and put into practice in the context of Islamic religious education. This article discusses the meaning and implementation of Sunan Gunung Jati's "ingsun entrusts tajug and the poor" in contextual learning in Islamic Religious Education (PAI). This testament contains an important message about the importance of maintaining a balance between human relationships with Allah Swt (hablum minallah) and human relationships with fellow humans (hablum minannas). PAI contextual learning emphasizes the relationship between theory and practice in real life. The testament "ingsun entrusts tajug and the poor" can be used as a basis for developing more effective and meaningful PAI contextual learning. This research uses a qualitative method with a phenomenological approach. The phenomenological approach emphasizes the direct description of individual subjective experiences. This means researchers seek to understand human experience directly through observation, interviews, or direct experience. This means the researcher seeks to understand the essence or core meaning of the individual experience or phenomenon being studied. The aim of this research is to provide a basis for developing curriculum and learning practices that are oriented towards character development and a holistic understanding of religion, as well as being able to interpret Islamic religious education learning in a contextual form. Keywords: Contextual learning; Islamic Religious Education; Will ingsun titip tajug lan fakir miskin